Anticancer Activity in Honeybee Propolis: Functional Insights to the Role of Caffeic Acid Phenethyl Ester and Its Complex With γ-Cyclodextrin. (September 2018) - Ishida, Yoshiyuki; Gao, Ran; Shah, Navjot; Bhargava, Priyanshu; Furune, Takahiro; Kaul, Sunil C.; Terao, Keiji; Wadhwa, Renu
Besides honey, honeybees make a sticky substance (called propolis/bee glue) by mixing saliva with poplar tree resin and other botanical sources. It is known to be rich in bioactivities of which the anticancer activity is most studied. Caffeic acid phenethyl ester (CAPE) is a key anticancer component in New Zealand propolis. We have earlier investigated the molecular mechanism of anticancer activity in CAPE and reported that it activates DNA damage signaling in cancer cells. CAPE-induced growth arrest of cells was mediated by downregulation of mortalin and activation of p53 tumor suppressor protein. When antitumor and antimetastasis activities of CAPE were examined in vitro and in vivo, we failed to find significant activities, which was contrary to our expectations. On careful examination, it was revealed that CAPE is unstable and rather gets easily degraded into caffeic acid by secreted esterases. Interestingly, when CAPE was complexed with γ-cyclodextrin (γCD) the activities were significantly enhanced. In the present study, we report that the CAPE-γCD complex with higher cytotoxicity to a wide range of cancer cells is stable in acidic milieu and therefore recommended as an anticancer amalgam. We also report a method for preparation of stable and less-pungent powder of propolis that could be conveniently used for health and therapeutic benefits.